PENGARUH TANGGAPAN KONSUMEN TERHADAP RITEL MODERN BARU 2010 DI KOTA SEMARANG TERHADAP PERUBAHAN PERILAKU PEMBELIAN (Studi Perempuan Pekerja di Semarang) - Michelle Indriyanti Supatra; Berta Bekti Retnawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2009)
This study aims to analysis responses women workers in new retail presence in the city of Semarang. The type of data used are primary data using questionnaire data collection method that guided the interviews. As for the data analysis techniques, for the shopping habits of respondents before the new modern retail, the response to the new modern retail 7P viewed from the side, so that it could be concluded about the spending habits of behavior had changed after the new modern retail. The conclusion of this study, only a few respondents who intend to move to new modern retail, though seen some positive findings from both these retail. Suggestions provided, before making a new retail, retail manager must select the consumer that will be addressed and also study the characteristics of existing customers in the city of Semarang that retail businesses can survive and become a favorite shopping place for consumers.